2017
DOI: 10.1136/bmjgh-2017-000348
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying unmet need for hypertension care in South Africa through a care cascade: evidence from the SANHANES, 2011-2012

Abstract: IntroductionHypertension has become a major cause of morbidity and premature mortality in South Africa, but population-wide estimates of prevalence and access to care are scarce. Using data from the South African National Health and Nutrition Examination Survey (2011–2012), this analysis evaluates the national prevalence of hypertension and uses a care cascade to examine unmet need for care.MethodsHypertension was defined as blood pressure over 140/90 mm Hg or use of antihypertensive medication. We constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
114
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 25 publications
15
114
8
Order By: Relevance
“…Our absolute losses of -33% at screening, and -66% at diagnosis in Thailand are slightly better for screening and slightly worse for diagnosis compared to other diabetes care cascade studies in South Africa (absolute losses -45% at screening, -60% at diagnosis), and globally in 28 low-and-middle income countries (absolute losses -37% at screening, -56% at diagnosis) https://doi.org/10.1371/journal.pone.0226286.g003 [12][13][14]. The United States fares the worst among these cascades, with an absolute loss of -72% at diagnosis [16].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our absolute losses of -33% at screening, and -66% at diagnosis in Thailand are slightly better for screening and slightly worse for diagnosis compared to other diabetes care cascade studies in South Africa (absolute losses -45% at screening, -60% at diagnosis), and globally in 28 low-and-middle income countries (absolute losses -37% at screening, -56% at diagnosis) https://doi.org/10.1371/journal.pone.0226286.g003 [12][13][14]. The United States fares the worst among these cascades, with an absolute loss of -72% at diagnosis [16].…”
Section: Discussionmentioning
confidence: 68%
“…Care cascades were originally used to model loss to follow up in HIV/AIDS care and have subsequently been applied to a range of other chronic conditions, including hypertension and diabetes [10,11]. Prior studies using data across multiple LMIC, for example, revealed large gaps between screening and diagnosis, with 80% unmet need in diabetes care [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We treated missing data, therefore, as itself a result rather than the absence of findings. However, in addition to evaluating SEARCH's effectiveness in HTN care relative to care delivery intent (i.e., its fidelity to the algorithm above), we also measured its impact in achieving key results in HTN control (i.e., its effect on care outcomes), via a series of steps validated in HTN control studies globally [42,43]. The cascade sequence of fidelity steps is displayed in the Results section.…”
Section: Approach and Analytic Planmentioning
confidence: 99%
“…In SA, hypertension is one of the leading causes of death, and 50% of treated hypertensive patients are not controlled. [17] In the USA, the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study showed that African Americans are more likely to be diagnosed with hypertension, more likely to be treated, more likely to be treated intensively, and less likely to achieve BP control. [18] Although the reasons are complex, including poor adherence and lack of access to antihypertensive medication, it is now apparent that a large proportion of uncontrolled hypertension in blacks is due to polymorphisms in genes that increase ENaC function, resulting in salt and water retention, with suppressed renin and aldosterone.…”
Section: Case For Amiloride In South Africamentioning
confidence: 99%